2019
DOI: 10.3390/cancers11121856
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Use of Beta-Blockers Is Associated with Outcome of Metastatic Colorectal Cancer Patients Treated with Bevacizumab-Based Therapy: A Single-Institution Retrospective Analysis of 514 Patients

Abstract: Background: Beta-adrenergic signalling plays an important role in several cancer-related processes, including angiogenesis. The impact of beta-blocker use on prognosis of cancer patients treated with antiangiogenic agents is unclear. The aim of this study was to evaluate the association between the incidental use of beta-blockers and the outcomes of patients with metastatic colorectal cancer (mCRC) treated with bevacizumab-based therapy. Methods: Clinical data from 514 mCRC patients treated with bevacizumab be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Fiala et al [ 18 ] reported the clinical outcome of 514 mCRC patients treated with bevacizumab, stratified by incidental use of beta blockers; 126 patients (24%) were incidental beta-blocker users. Median progression free survival (mPFS) for beta-blocker users vs. not were respectively 11.4 vs. 8.3 months ( p = 0.006), whereas mOS were respectively 26.8 vs. 21.0 ( p = 0.009).…”
Section: Resultsmentioning
confidence: 99%
“…Fiala et al [ 18 ] reported the clinical outcome of 514 mCRC patients treated with bevacizumab, stratified by incidental use of beta blockers; 126 patients (24%) were incidental beta-blocker users. Median progression free survival (mPFS) for beta-blocker users vs. not were respectively 11.4 vs. 8.3 months ( p = 0.006), whereas mOS were respectively 26.8 vs. 21.0 ( p = 0.009).…”
Section: Resultsmentioning
confidence: 99%
“…For metastatic colorectal cancer, an observational study with 514 reported that β-blockers in combination with bevacizumab, a monoclonal antibody directed against VEGF-A, increased median overall survival and progression-free survival compared to treatment only with bevacizumab ( 143 ).…”
Section: Renin-angiotensin System-based Drugsmentioning
confidence: 99%
“…A study of 14,166 patients indicated that long-term diuretics therapy might increase colon cancer-specific mortality ( Tenenbaum et al, 2001 ). A population-based study, with a follow-up time of 6.6 years, supported that pre- or post-diagnostic BB intake was not related with colorectal cancer prognosis ( Jansen et al, 2017 ), but a recent study suggested BB might improve overall survival (OS) ( Fiala et al, 2019 ). In addition, a cohort study from Shanghai proposed that ARB and BB usage were associated with better survival in colorectal cancer patients ( Cui et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%